Graphite fiber and preparation method thereof
In the process of wet spinning, cellulose and alginate are used to improve the orientation and compactness of the graphene layer sheet, and stable graphite fibers are formed through cross-linking reactions, which solves the problems of defects and holes in the fibers, and achieves both high strength and high toughness.
Patent Information
- Application Number
- CN202411946241.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
There are defects and holes in the process of wet spinning to prepare graphene fibers, which affects its mechanical and electrical properties, and it is difficult to accurately control the orientation and compactness of the graphene layer during traction and stretching.
By mixing the peeled graphene, cellulose dispersion and alginate dispersion, a spinning stock solution is formed and dried in a solidification bath. The orientation and density of the graphene layer sheet are enhanced by using the reticular structure of the cellulose and the liquid crystal induction effect of the alginate, and stable graphite fibers are formed through cross-linking reaction.
The problem of contradictory strength and toughness of artificial fiber structural materials is effectively solved. The obtained graphite fibers take into account both good mechanical properties and thermal conductivity, with reduced surface roughness and porosity.
Smart Images

Figure CN119640438A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials and relates to a graphite fiber and a preparation method thereof. Background Art
[0002] In the field of emerging materials, continuous long fibers with diameters ranging from tens to hundreds of microns have shown broad application potential in many high-tech and traditional industrial fields due to their excellent mechanical properties.
[0003] For a long time, long fibers with extraordinary mechanical properties have mainly relied on synthetic polymer fibers, such as polyacrylonitrile fibers and Kevlar fibers. These synthetic fibers achieve high strength, high modulus and other properties through precise chemical synthesis and complex processing, thus meeting the needs of a variety of high-end applications. However, with the increasing awareness of environmental protection, the problem of the difficulty of degrading synthetic polymer fibers after the end of their life cycle has gradually become prominent, causing a negative impact on the environment that cannot be ignored. In contrast, bio-derived fibers have better biodegradability, renewability, low density and a wide range of sources, which provide more possibilities for the customization and diversified application of fibers, but at present, bio-derived fibers are still subject to their relatively weak mechanical properties.
[0004] In addition to the above problems, for the mechanical properties of long fibers themselves, the two properties of strength and toughness often show a trend of mutual exclusion. Generally speaking, to achieve sufficiently high strength, it is often necessary to sacrifice its elongation and toughness. Therefore, how to solve the defects of the contradiction between strength and toughness in order to better balance high tensile strength, large elongation and toughness is also the focus of researchers.
[0005] As a new type of high-performance fiber material, graphite fiber has received extensive attention and research in recent years. With its unique graphite structure and high electrical and thermal conductivity, graphite fiber has shown great application potential in the fields of electronics, energy, aerospace, etc. Especially in terms of mechanical properties, graphite fiber has great potential to achieve both high strength and high toughness, which is mainly due to the arrangement and orientation of its internal graphite materials (such as graphene and graphene oxide, etc.), and these factors are directly related to the preparation process of graphite fiber.
[0006] At present, the industry has developed a variety of effective preparation methods. Among them, wet spinning has become one of the most widely used solutions for large-scale practical applications due to its advantages such as simple process, low cost, and easy large-scale production. The general process of preparing graphene fibers by wet spinning includes the preparation of graphene oxide dispersion, the preparation of spinning solution, the spinning process, the coagulation and washing of the primary fibers, and subsequent heat treatment or chemical reduction. Through these steps, graphene fibers with a certain length and diameter can be prepared.
[0007] However, there are still some urgent problems to be solved in the process of preparing graphene fibers by wet spinning. First, due to the irregular size and shape of graphene oxide and the weak interfacial force between graphene layers, the double diffusion process of the spinning solution is slow when solidifying in the coagulation bath, which easily introduces a large number of defects and voids. These defects and voids will seriously affect the mechanical and electrical properties of the macroscopic fiber, making it significantly different from the performance of the single-sheet graphene material. Secondly, although the orientation and density of the graphene unit in the fiber can be improved by the stretching of external force, thereby improving the mechanical and electrochemical properties of the fiber, for one-dimensional graphite fibers, the traction force during traction stretching is difficult to accurately control on each graphene layer. In addition, the graphene layer is prone to wrinkles and slippage during the stretching process, resulting in uneven fiber thickness, and it is difficult to achieve regular arrangement and high densification of graphene sheets. These problems greatly hinder the transmission of the excellent microscopic properties of graphene to macroscopic fiber materials, which limits the practical application of graphene fibers.
[0008] Therefore, in view of the problems existing in the process of preparing graphene fibers by wet spinning, further research and development of graphite fibers and their preparation schemes are needed to further achieve the balance between high strength and high toughness, and provide support for promoting the application and development of graphite fibers in more fields. Summary of the invention
[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a graphite fiber and a preparation method thereof, the preparation method comprising mixing exfoliated graphene, cellulose dispersion and alginate dispersion to obtain a spinning solution; then extruding the spinning solution into a coagulation bath, and drying to obtain the graphite fiber. The cellulose dispersion is used to stably exfoliate the graphene, effectively disperse and exfoliate the graphite sheets; at the same time, cellulose has a natural mesh structure, and the exfoliated graphene can be modified to obtain a preliminary fiber structure; alginate is used as a liquid crystal inducer to generate exfoliated graphene / sodium alginate nematic liquid crystals, which can effectively improve the orientation and density of the graphene sheets, and at the same time, a wet spinning coagulation bath is introduced to crosslink the exfoliated graphene / sodium alginate to obtain graphite fibers. The preparation method can effectively solve the problem of the contradiction between the strength and toughness of artificial fiber structural materials, and the obtained exfoliated graphene-cellulose-alginate composite large fibers have both good mechanical properties and thermal conductivity.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing graphite fiber, comprising:
[0012] (1) mixing the exfoliated graphene, cellulose dispersion and alginate dispersion to obtain a spinning solution;
[0013] (2) Extruding the spinning solution into a coagulation bath and then drying it to obtain the graphite fiber.
[0014] The present invention finds that graphene can be effectively and stably exfoliated by adding cellulose dispersion, and the interaction between cellulose and graphite sheets can effectively disperse and exfoliate graphite sheets; at the same time, cellulose has a natural mesh structure. After adding and using cellulose, the exfoliated graphene can be modified by using cellulose as a matrix to obtain a preliminary fiber structure. Then, a natural polysaccharide material alginate material is used as a liquid crystal inducer, and only a small amount of alginate is needed to generate exfoliated graphene / alginate nematic liquid crystals, which can effectively improve the orientation and density of graphene flakes. Then, by introducing a coagulation bath of wet spinning, the exfoliated graphene / sodium alginate undergoes a cross-linking reaction, and then a stable system is formed to cross-link and fix the graphene flakes to obtain a graphite fiber product. The graphite fiber obtained by the preparation and method is an exfoliated graphene-cellulose-alginate composite large fiber, which takes into account excellent mechanical properties and thermal conductivity. Through the "wet orientation method" of the present invention, the surface roughness of the obtained graphite fiber can be reduced, the porosity can be reduced, the orientation degree of the layer can be improved, the electrical and mechanical properties of the graphite fiber can be enhanced, and the defect of the current contradiction between strength and toughness of artificial fiber structural materials can be solved.
[0015] It should be further explained that the cellulose dispersion in the present invention refers to a substance obtained by dispersing cellulose in a solvent, such as water or ethanol, etc. The type of the solvent is not limited as long as the cellulose can be dispersed.
[0016] It should be further explained that the alginate dispersion in the present invention refers to a substance obtained by dispersing alginate in a solvent, such as water or ethanol, etc. The type of the solvent is not limited as long as it can disperse cellulose.
[0017] It should be further explained that the exfoliated graphene / alginate nematic liquid crystal in the present invention refers to the nematic liquid crystal in which the direction of the graphite sheets induced by sodium alginate grows and arranges along the direction perpendicular to the cross section under the action of the extrusion force of the spinning solution.
[0018] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0019] As a preferred technical solution of the present invention, the method for preparing the exfoliated graphene comprises:
[0020] (1) subjecting a graphite raw material to a pre-oxidation heat treatment to obtain graphite oxide;
[0021] (2) After mixing the graphite oxide with the exfoliating agent dispersion, the mixture is sand-milled and centrifuged to obtain exfoliated graphene.
[0022] As a preferred technical solution of the present invention, in step (1), in step (1), in the spinning solution, the total mass of the exfoliated graphene, cellulose and alginate is 100%, the mass of the exfoliated graphene accounts for 49% to 80%, for example, it can be 49%, 50%, 53%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 75%, 78% or 80%; the mass of cellulose accounts for 1% to 2%, for example, it can be 1%. , 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc.; the mass of alginate accounts for 19% to 49%, for example, it can be 19%, 20%, 23%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 49%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0023] Preferably, the alginate in the alginate dispersion includes at least one of sodium alginate, potassium alginate, calcium alginate or ammonium alginate.
[0024] Preferably, the cellulose in the cellulose dispersion includes at least one of carboxymethyl cellulose and hydroxymethyl cellulose.
[0025] Preferably, the preparation method comprises first mixing the exfoliated graphene with the cellulose dispersion to obtain a suspension; and then mixing the suspension with the alginate dispersion to obtain a spinning solution.
[0026] As a preferred technical solution of the present invention, in step (2), a cross-linking auxiliary agent dispersion is used in the coagulation bath.
[0027] Preferably, the concentration of the crosslinking aid in the crosslinking aid dispersion is 0.1 to 2.0 mol / L, for example, 0.1 mol / L, 0.3 mol / L, 0.50 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L or 2 mol / L, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0028] Preferably, the cross-linking aid comprises a soluble calcium salt.
[0029] Preferably, the soluble calcium salt comprises CaCl2.
[0030] The calcium ions in the cross-linking auxiliary agent of the present invention can generate ionic cross-linking with alginate, thereby causing the exfoliated graphene / alginate to undergo cross-linking to form a stable system to fix the exfoliated graphene, thereby obtaining graphite fibers.
[0031] Preferably, the solvent of the cross-linking aid dispersion includes ethanol and water.
[0032] Preferably, the volume ratio of ethanol to water is 1:(2-4), for example 1:2, 1:2.3, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0033] As a preferred technical solution of the present invention, in step (2), the coagulation bath is to extrude the spinning solution into the cross-linking auxiliary agent dispersion to obtain raw fibers, and then the obtained raw fibers are dried.
[0034] Preferably, the drying process includes fixing the two ends of the raw silk and performing directional low-temperature drying at a temperature ≤ 60°C to obtain dry silk, for example, 60°C, 58°C, 55°C, 52°C, 50°C, 48°C, 45°C, 42°C, 40°C, 38°C, 35°C, 32°C, 30°C, 28°C or 25°C, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0035] As a preferred technical solution of the present invention, the preparation method further comprises washing the raw silk or the dried silk to remove the cross-linking auxiliary agent.
[0036] In the present invention, after the graphite fiber is prepared, it is washed to remove the crosslinking agent, so the content of the crosslinking agent in the final graphite fiber product can be ignored.
[0037] As a preferred technical solution of the present invention, in step S1, the graphite raw material includes at least one of recycled graphite, expanded graphite, oxidized graphite or natural flake graphite.
[0038] Preferably, the graphite raw material is an ultrafine powder with a particle size Dv50 of 4 to 5 μm, for example, 4 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm or 5 μm, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0039] As a preferred technical solution of the present invention, in step S1, the temperature of the pre-oxidation heat treatment is 400-500°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C or 500°C, and the time is 3-7h, for example, 3h, 3.3h, 3.5h, 3.7h, 4h, 4.2h, 4.5h, 4.8h, 5h, 5.3h, 5.5h, 5.8h, 6h, 6.3h, 6.5h, 6.8h or 7h, but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0040] Preferably, the pre-oxidation heat treatment is performed in air or oxygen atmosphere.
[0041] In the present invention, the graphite raw material is preferably subjected to a pre-oxidation heat treatment, which can expand the graphite and facilitate the subsequent intercalation and stripping of the graphite by the stripping agent.
[0042] As a preferred technical solution of the present invention, in step S2, the stripping agent in the stripping agent dispersion includes cellulose.
[0043] Preferably, the cellulose includes at least one of carboxymethyl cellulose and hydroxymethyl cellulose.
[0044] The present invention utilizes the non-covalent interaction between cellulose and graphene nanosheets, and this interaction can effectively disperse and peel off graphite sheets, that is, the graphite raw material can be peeled off by cellulose to obtain peeled graphene materials, and can also be used to stabilize the graphene flakes obtained by peeling; at the same time, cellulose has a natural network structure, and after mixing it with peeled graphene, cellulose can be used as a matrix to modify the peeled graphene, so that it can obtain a preliminary fiber structure, which is conducive to the subsequent liquid crystal template agent to further induce it to form nematic liquid crystals. It should be noted that when cellulose is used as a peeling agent to peel off the graphite raw material, the amount of cellulose is not limited, and it is reasonably adjusted for the purpose of achieving the target peeling effect. Since the peeled graphene after peeling will undergo solid-liquid separation and washing operations, the peeling agent is easily removed, so the amount of cellulose used as a peeling agent does not affect the content of the final graphite fiber component.
[0045] As a preferred technical solution of the present invention, in step S2, the sanding time is 10 to 180 min, for example, 10 min, 20 min, 35 min, 50 min, 75 min, 90 min, 110 min, 130 min, 150 min or 180 min, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0046] Preferably, the grinding balls used for the sand grinding include zirconium balls with a particle size of 0.1 to 3 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm or 3 μm, but are not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0047] As a preferred technical solution of the present invention, in step S2, the centrifugal speed is 3000-5000rpm, for example, 3000rpm, 3200rpm, 3500rpm, 3800rpm, 4000rpm, 4200rpm, 4500rpm, 4800rpm or 5000rpm, and the time is 15-25min, for example, 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min or 25min, but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0048] Preferably, the method for preparing the exfoliated graphene also includes collecting the supernatant containing the exfoliated graphene after the centrifugation, and then subjecting the supernatant to high-speed centrifugation to obtain a precipitate of the exfoliated graphene; the rotation speed of the high-speed centrifugation is 12000-18000rpm, for example, 12000rpm, 13000rpm, 14000rpm, 15000rpm, 16000rpm, 17000rpm or 18000rpm, etc., and the time is 30-60min, for example, 30min, 35min, 40min, 45min, 50min, 55min or 60min, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0049] In a second aspect, the present invention provides a graphite fiber, wherein the graphite fiber is prepared by the preparation method described in the first aspect.
[0050] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0051] The preparation method of the present invention uses cellulose dispersion to stably exfoliate graphene, effectively disperse and exfoliate graphite sheets; cellulose has a natural mesh structure, and the exfoliated graphene can be modified to obtain a preliminary fiber structure; alginate is used as a liquid crystal inducing agent to generate exfoliated graphene / sodium alginate nematic liquid crystals, which can effectively improve the orientation and density of graphene sheets, and at the same time, a wet spinning coagulation bath is introduced to crosslink the exfoliated graphene / sodium alginate to obtain graphite fibers. The preparation method can effectively solve the problem of the contradiction between the strength and toughness of artificial fiber structural materials, and the obtained exfoliated graphene-cellulose-alginate composite large fiber has good mechanical properties and thermal conductivity, and is a low-cost and environmentally friendly graphite fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is the SEM test image of the peeled graphene in Example 1.
[0053] Figure 2 This is a SEM test image of the ultrafine powder of natural flake graphite, the graphite raw material of Example 1.
[0054] Figure 3 This is a SEM test image of the graphite fiber of Example 1.
[0055] Figure 4 This is a physical picture of the graphite fiber obtained in Example 1.
[0056] Figure 5 It is a schematic diagram of the load tensile test of the graphite fiber obtained in Example 1. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0058] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0059] Example 1
[0060] This embodiment provides a method for preparing graphite fiber, the preparation method comprising:
[0061] Step S1, taking ultrafine powder of natural flake graphite with a particle size of 4 to 5 μm as a graphite raw material, putting it into a CVD furnace, and performing a pre-oxidation heat treatment for 6 hours in an air atmosphere at 450° C. to obtain oxidized graphite.
[0062] 30 g of carboxymethyl cellulose (CMC) nanocrystals were weighed as a stripping agent, dissolved in deionized water by ultrasonication, and the volume was fixed to 1000 mL to obtain a stripping agent dispersion.
[0063] Step S2, adding 10 g of graphite oxide to the stripping agent dispersion, stirring at high speed and ultrasonic for 6 h at 25 ° C, then transferring 1 kg of the solution to a sand mill, adding zirconium balls with a particle size of 1 to 2 μm, and sand milling at 25 ° C for 60 min to obtain a suspension.
[0064] The treated suspension was subjected to primary centrifugation for 20 min at a speed of 4000 rpm to remove the unexfoliated graphite raw material. After the primary centrifugation, the supernatant (i.e., the aqueous dispersion containing exfoliated graphene) was taken out with a pipette for later use. The supernatant after multiple primary centrifugations was collected, and then high-speed centrifugation was performed at a speed of 15000 rpm for 60 min to collect the precipitate (i.e., exfoliated graphene).
[0065] Step (1), weighing 1 g of CMC as a dispersant and dissolving it in 78 g of water to obtain a cellulose dispersion, and then weighing 30 g of the obtained exfoliated graphene and adding it thereto to obtain a suspension.
[0066] 37.5 g of sodium alginate was weighed as a liquid crystal template and dissolved in 600 mL of water in four times to obtain an alginate dispersion.
[0067] The obtained suspension is mixed with the alginate dispersion to obtain a spinning solution; in the spinning solution, based on the total mass of the exfoliated graphene, cellulose and sodium alginate being 100%, the mass of the exfoliated graphene accounts for 43.80%, the mass of the cellulose accounts for 1.46%, and the mass of the sodium alginate accounts for 54.74%.
[0068] Step (2), weigh 11.1 g of calcium chloride as a crosslinking aid, dissolve it in 1000 mL of water to obtain a crosslinking aid dispersion, the concentration of the crosslinking aid is 0.1 mol / L.
[0069] The spinning solution is squeezed into the cross-linking auxiliary agent dispersion to carry out a cross-linking reaction to obtain a raw fiber; the two ends of the obtained raw fiber are fixed, and directional low-temperature drying is carried out at 55°C to obtain dry graphite fiber.
[0070] Example 2
[0071] The present embodiment provides a method for preparing graphite fiber. In the preparation method, in step (1), the amount of exfoliated graphene is adjusted from 30 g to 25 g, and the amount of sodium alginate is adjusted from 37.5 g to 42.5 g, so that in the spinning solution, the mass proportion of exfoliated graphene is adjusted from 43.80% to 36.50%, and the mass proportion of sodium alginate is adjusted from 54.74% to 62.04%. Except for the above, other conditions are exactly the same as those in Example 1.
[0072] Example 3
[0073] The present embodiment provides a method for preparing graphite fiber. In the preparation method, in step (1), the amount of exfoliated graphene is adjusted from 30 g to 42 g, and the amount of sodium alginate is adjusted from 37.5 g to 25.5 g, so that in the spinning solution, the mass proportion of exfoliated graphene is adjusted from 43.80% to 61.31%, and the mass proportion of sodium alginate is adjusted from 54.74% to 37.23%. Except for the above, other conditions are exactly the same as those in Example 1.
[0074] Example 4
[0075] The present embodiment provides a method for preparing graphite fiber. In the preparation method, in step (1), the amount of exfoliated graphene is adjusted from 30 g to 54 g, and the amount of sodium alginate is adjusted from 37.5 g to 13.5 g, so that in the spinning solution, the mass proportion of exfoliated graphene is adjusted from 43.80% to 78.83%, and the mass proportion of sodium alginate is adjusted from 54.74% to 19.71%. Except for the above, other conditions are exactly the same as those in Example 1.
[0076] Example 5
[0077] The present embodiment provides a method for preparing graphite fiber. In the preparation method, in step (1), the amount of exfoliated graphene is adjusted from 30 g to 60 g, and the amount of sodium alginate is adjusted from 37.5 g to 7.5 g, so that in the spinning solution, the mass proportion of exfoliated graphene is adjusted from 43.80% to 87.59%, and the mass proportion of sodium alginate is adjusted from 54.74% to 10.95%. Except for the above, other conditions are exactly the same as those in Example 1.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing graphite fiber, in which sodium alginate is replaced by PVP. Except for the above, other conditions are exactly the same as those in Example 1.
[0080] Comparative Example 2
[0081] This comparative example provides a method for preparing graphite fiber. In step (1) of the preparation method, CMC is not used as a dispersant, that is, the amount of the dispersant CMC is adjusted from 1g to 0g. Except for the above, other conditions are exactly the same as those in Example 1.
[0082] Comparative Example 3
[0083] This comparative example provides a method for preparing graphite fiber. In step (2) of the preparation method, there is no extrusion process, that is, the cross-linking auxiliary agent dispersion is added to the spinning solution instead. Other conditions are exactly the same as those in Example 1.
[0084] Characterization and testing
[0085] Ⅰ. Morphological characterization:
[0086] Figure 1 This is the SEM test image of the peeled graphene in Example 1. Figure 2 This is a SEM test image of the ultrafine powder of natural flake graphite, the graphite raw material of Example 1. Figure 1 and Figure 2 It can be seen that the graphite changes from block to uniform flake, indicating that the graphite is exfoliated. Figure 3 is a SEM test image of the graphite fiber of Example 1, Figure 3 It can be seen that the graphene sheets are arranged along the radial direction in the liquid crystal of sodium alginate.
[0087] Figure 4 is a physical picture of the graphite fiber obtained in Example 1, Figure 4 It can be seen that the obtained graphite can be wrapped around objects and has a certain toughness. The obtained graphite fiber is a composite large fiber. The actual picture is as follows Figure 5 shown.
[0088] Ⅱ. Mechanical properties test:
[0089] The tensile properties of the samples were tested using a biomechanical testing machine (23MTSInsight, USA), and the stress-strain curve was obtained to calculate the tensile strength, strain at break, modulus, and toughness of the samples. The test was carried out at room temperature and relative humidity (50% RH), with a tensile rate of 5 mm / min, a sample length of approximately 50 mm, and a gauge length of 20 mm. The cross-sectional area of the fiber was calculated using an optical microscope. Each group of samples was tested 3 times, and the average value was taken to ensure the repeatability of the experimental results.
[0090] The results are recorded in Table 1.
[0091] Table 1
[0092] Group Tensile strength(MPa) Fiber diameter (μm) Example 1 460 56 Example 2 393 49 Example 3 367 48 Example 4 355 57 Example 5 342 62 Comparative Example 1 336 59 Comparative Example 2 322 71 Comparative Example 3 Not getting fiber 200
[0093] It can be seen from Table 1 that exfoliated graphite can effectively enhance the tensile strength of graphite fiber. When the exfoliated graphite content is high, the graphite fiber has insufficient toughness and is easily broken. When the exfoliated graphite content is low, the graphite fiber has uneven mechanical strength and is easily broken. The uniform dispersion of exfoliated graphite can give full play to the advantages of the lamellar structure of exfoliated graphite to enhance the mechanical strength. If the coagulation bath is directly added to the spinning solution, flocculent floating materials will be generated and fiber cannot be formed.
[0094] In summary, in the graphite fiber described in the present invention, by adding the liquid crystal template agent, it induces the exfoliation of graphene, and together with the exfoliated graphene, forms an exfoliated graphene / liquid crystal template nematic liquid crystal, effectively improving the orientation density of the graphene layer. By adding a cross-linking auxiliary agent that can cross-link with the liquid crystal template agent, the cross-linking auxiliary agent and the nematic liquid crystal form a cross-linked body, thereby obtaining a stable graphite fiber. The graphite fiber has a low surface roughness and a small porosity, and takes into account both strength and toughness. It is a composite large fiber material with excellent mechanical properties and thermal conductivity.
[0095] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0096] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0097] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing graphite fiber, characterized in that: include: (1) mixing the exfoliated graphene, cellulose dispersion and alginate dispersion to obtain a spinning solution; (2) Extruding the spinning solution into a coagulation bath and then drying it to obtain the graphite fiber.
2. The preparation method according to claim 1, characterized in that: The method for preparing the exfoliated graphene comprises: S1, pre-oxidation heat treatment of graphite raw material to obtain oxidized graphite; S2. After mixing the graphite oxide with the stripping agent dispersion, the mixture is sand-milled and centrifuged to obtain stripped graphene.
3. The preparation method according to claim 1, characterized in that: In step (1), in the spinning solution, based on the total mass of the exfoliated graphene, cellulose and alginate as 100%, the mass of the exfoliated graphene accounts for 49% to 80%, the mass of the cellulose accounts for 1% to 2%, and the mass of the alginate accounts for 19% to 49%; Preferably, the alginate in the alginate dispersion includes at least one of sodium alginate, potassium alginate, calcium alginate or ammonium alginate; Preferably, the cellulose in the cellulose dispersion includes at least one of carboxymethyl cellulose and hydroxymethyl cellulose.
4. The preparation method according to claim 1, characterized in that: In step (2), a cross-linking auxiliary agent dispersion is used in the coagulation bath; Preferably, the concentration of the crosslinking aid in the crosslinking aid dispersion is 0.1 to 2.0 mol / L; Preferably, the cross-linking aid comprises a soluble calcium salt; Preferably, the soluble calcium salt comprises CaCl2; Preferably, the solvent of the crosslinking aid dispersion includes ethanol and water; Preferably, the volume ratio of ethanol to water is 1:(2-4).
5. The preparation method according to claim 2, characterized in that: In step S1, the graphite raw material includes at least one of recycled graphite, expanded graphite, oxidized graphite or natural flake graphite; Preferably, the graphite raw material is ultrafine powder with a particle size Dv50 of 4 to 5 μm.
6. The preparation method according to claim 2, characterized in that: In step S1, the pre-oxidation heat treatment is performed at a temperature of 400 to 500° C. for a time of 3 to 7 hours; Preferably, the pre-oxidation heat treatment is performed in air or oxygen atmosphere.
7. The preparation method according to claim 2, characterized in that: In step S2, the stripping agent in the stripping agent dispersion includes cellulose; Preferably, the cellulose includes at least one of carboxymethyl cellulose and hydroxymethyl cellulose.
8. The preparation method according to claim 2, characterized in that: In step S2, the sanding time is 10 to 180 minutes; Preferably, the grinding balls used in the sand grinding include zirconium balls with a particle size of 0.1 to 3 μm.
9. The preparation method according to claim 2, characterized in that: In step S2, the centrifugal speed is 3000-5000 rpm and the time is 15-25 min.
10. A graphite fiber, characterized in that: The graphite fiber is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of graphene oxide / sodium alginate liquid crystal composite solution
CN105237816A
Preparing method of modified graphene fiber
CN109868527A
Graphene preparation method
CN110240152A